Computational Fluid Dynamics Modeling of Fermentation Reactions in Bioethanol Fermentor: A Review - Wijaya, Ali Satria; Novia, Novia; Hadiah, Fitri (Journal of Applied Materials and Technology, 2023)
Bioethanol is a renewable energy source that can replace fossil fuels. The advantages in terms of economy and its impact on the environment make bioethanol was chosen as a biofuel. Bioethanol can be produced from various types of biomasses with the help of microorganisms, namely yeast, for the fermentation process. In manufacturing, factors including temperature, concentration, pH, fermentation time, and stirring speed influence the fermentation process. Computational Fluid dynamics (CFD) package can be applied to observe the procedures in a fermenter. CFD simulates fluid movement, energy transport, chemical reactions, and other phenomena with the aim of clarifying their impact on the overall effectiveness of bioethanol production. In this journal, a review of the fermentation process with CFD modeling was made to look at the parameters and phenomena during the bioethanol production process. The analysis commences with an examination of the processes involved in bioethanol production and underscores the crucial role of fermentation in transforming renewable resources into bioethanol. Subsequently, it delves into the foundational principles of CFD and how they are incorporated into the modeling of bioethanol fermenters. Furthermore, the review highlights key advancements and innovations in CFD modeling techniques, such as multiphase models, turbulence modeling, and coupled simulations, aiming to capture the intricate interplay of physical and biological phenomena within fermentors. Insights into the impact of operating conditions, reactor design, and microbial behavior on bioethanol yield and quality are discussed, providing a comprehensive understanding of the complex system dynamics.